Brain Motor Network Changes in Parkinson's Disease: Evidence from Meta‐Analytic Modeling - Herz, Damian M.; Meder, David; Camilleri, Julia A.; Eickhoff, Simon B.; Siebner, Hartwig R. (Movement disorders, 2021)
Background Motor‐related brain activity in Parkinson's disease has been investigated in a multitude of functional neuroimaging studies, which often yielded apparently conflicting results. Our previous meta‐analysis did not resolve inconsistencies regarding cortical activation differences in Parkinson's disease, which might be related to the limited number of studies that could be included. Therefore, we conducted a revised meta‐analysis including a larger number of studies. The objectives of this study were to elucidate brain areas that consistently show abnormal motor‐related activation in Parkinson's disease and to reveal their functional connectivity profiles using meta‐analytic approaches. Methods We applied a quantitative meta‐analysis of functional neuroimaging studies testing limb movements in Parkinson's disease comprising data from 39 studies, of which 15 studies (285 of 571 individual patients) were published after the previous meta‐analysis. We also conducted meta‐analytic connectivity modeling to elucidate the connectivity profiles of areas showing abnormal activation. Results We found consistent motor‐related underactivation of bilateral posterior putamen and cerebellum in Parkinson's disease. Primary motor cortex and the supplementary motor area also showed deficient activation, whereas cortical regions localized directly anterior to these areas expressed overactivation. Connectivity modeling revealed that areas showing decreased activation shared a common pathway through the posterior putamen, whereas areas showing increased activation were connected to the anterior putamen. Conclusions Despite conflicting results in individual neuroimaging studies, this revised meta‐analytic approach identified consistent patterns of abnormal motor‐related activation in Parkinson's disease. The distinct patterns of decreased and increased activity might be determined by their connectivity with different subregions of the putamen. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.